Системно-аналітичне забезпечення, як управління розвитком кредитних спілок - Стоянов, Г.С. (Культура народов Причерноморья, 2014)
Стаття присвячена формуванню методичних підходів з удосконалення механізму розвитку кредитних спілок, виражених у виді системно-аналітичному забезпеченні розвитку кредитних спілок України. Дане забезпечення може бути використано при використанні при управління розвитком кредитних спілок та адаптуванні моделей покращення їх діяльності. У розрізі по блокам розписані властивості системи управління розвитком кредитних спілок. У статті представлена концептуальна схема сценарної, імітаційної, системно-динамічної моделі розвитку кредитних спілок з наведеним прикладом застосування в промислових умовах. В статье сформулированы методические подходы по усовершенствованию механизма развития кредитных союзов, выраженных в виде системно–аналитического обеспечения развития отечественных кредитных союзов. Данное обеспечение может быть использовано при управлении развития кредитных союзов и адаптации моделей улучшения их работы. В соответствии с блоками описаны свойства управления развитием кредитных союзов. В статье представлена концептуальная схема сценарной, имитационной, системно-динамической модели развития кредитных союзов с приведённым примером применения в промышленных условиях. The article is dedicated to the description of the methodical approaches of improving of the mechanism of Credit Unions` development expressed in the way of systemic analytical support of CU`s domestic market development. Such analytical background can be used in managing of CU`s development and applying effective models of their development. The classification of lost profit and the appraisal plan were presented in the work. The modeling procedure was described by showing the interaction of its components. The analysis of imperfect and incompleted strategical decisions was provided by the diagram of blocks. Researching basic hypotheses which is fixed in basis of the developed recommendations of improving of systemic activity and marketing innovative policy will count the followings suppositions: 1.We`ll consider the existent level of development of credit union of current period satisfactory. 2.The found out progress trends does not allow to consider its sufficient, because the nearest prospect on condition of existent level of development at the decline of business activity of clients will be characterized as negative. 3.The most substantial subzero lines of development, which are certain as the lost benefits and exactly on the removal of influence of which there will be the directed measures of marketing innovative strategy, are systematized and selected. The scripts of future developing of Credit Unions were also described.